Properties of Collagen Hydrolyzates Obtained from Leather Shavings - MOKREJS, PAVEL; SUKOP, SVATOPLUK; LANGMAIER, FERDINAND; KOLOMAZNIK, KAREL; MLADEK, MILAN (Asian Journal of Chemistry, 2010)
Hydrolyzates are low-molecular products obtained in the second stage of enzymatic hydrolysis of chrome-tanned leather shavings. It is necessary to know thermal properties of hydrolyzates, gels and films for their intended industrial applications, especially when processing them into packing materials. The object of the presented work is study of thermal properties of powdery hydrolyzates, gels of hydrolyzates prepared from 40% (w/w) solutions and films of hydrolyzates prepared from 12.5% (w/w) solutions with/without adding plasticizer (glycerin). Thermal properties (glass transition temperature, melting point of gels and melting point of films) were determined employing different scanning calorimetry and thermo mechanical analyzer.